Antimicrobial Activity Against Phytopathogens and Inhibitory Activity on Solanine in Potatoes of the Endophytic Bacteria Isolated From Potato Tubers - Liu, Jia-Meng; Wang, Shan-Shan; Zheng, Xu; Jin, Nuo; Lu, Jia; Huang, Ya-Tao; Fan, Bei; Wang, Feng-Zhong (Frontiers in Microbiology, 2020)
As a global important crop, the Potato (Solanum tuberosum L.) contains the endotoxin solanine that lead to human poisoning and major economic losses. Poisoning symptoms and even acute poisoning may occur when the content of solanine in potatoes exceeds 200 mg/kg. In addition, potatoes are susceptible to some pathogenic bacteria, including Streptomyces scabies and Erwinia carotovora subsp. atroseptica (Van Hall) Dye, which can cause potato scab and potato blackleg disease respectively. In this study, 37 culturable endophytic bacteria strains were obtained from the potato tubers based on the culture-dependent method. Among them, 9 strains showed antimicrobial activity against at least one pathogen by antimicrobial activity screening and 23 strains showed inhibitory activity on solanine in potato tubers. Among them, strain P-NA2-14 (Bacillus megaterium NBRC 15308 T , 99.31%) showed not only the better antimicrobial activity against both the two indicator pathogens, but also the best inhibitory activity on solanine, which was proved to be a potential biocontrol bacterium. Meanwhile, the relationships between the distribution of endophytic bacterial community and the content of solanine in potato tubers have been studied by Illumina-based analysis, indicating that the distribution of endophytic bacterial community was influenced by the content of solanine obviously. The results showed a new insight on relationship between plant secondary metabolites and endophytic bacteria in potato tubers and provided a potential new technical support for the biological control of potato storage.